The Plasma S-adenosylmethionine Level is Associated With the Severity of Hepatitis B-Related Liver Disease. Issue 4 (January 2015) - Li, Ting; Yu, Guozheng; Guo, Tao; Qi, Haolong; Bing, Yuntao; Xiao, Yusha; Li, Changsheng; Liu, Weijun; Yuan, Yufeng; He, Yueming; Liu, Zhisu; Liu, Quanyan; et al.
<x xml:space="preserve">Abstract</x> Abstract Alterations in methionine metabolism that involve changes in the plasma S-adenosylmethionine (SAMe) level occur in chronic liver diseases. However, no evidence is available on whether circulating SAMe is involved in the development of liver cirrhosis and liver cancer. Cross-sectional data on clinical characteristics and plasma SAMe were collected for 130 cases of chronic hepatitis B (CHB) and HCC as well as for normal volunteers. Univariate and multivariate linear regression and receiver operating characteristic curves were introduced to determine their correlations. Serum ALB and PT levels were independent clinical factors that were correlated with the plasma SAMe levels in CHB and HCC patients. A higher SAMe concentration was observed in the HCC than in the normal and CHB. By exploring the association of the Child–Pugh score with the plasma SAMe level, we found a higher SAMe level at advanced Stage C than at stage A in CHB and HCC patients. We further assessed the diagnostic performance of SAMe with respect to the stages of liver fibrosis and Child–Pugh stage. The AUROC of SAMe for the prediction of cirrhosis was 0.721, and the sensitivity and specificity was 0.707 and 0.769, respectively. The AUROC of plasma SAMe to predict Child–Pugh stage C was 0.706 in patients with CHB and 0.825 in HCC patients. The sensitivity was 0.467 and 0.800, respectively; the specificity was 0.904 and 0.781, respectively. The plasma SAMe level was positively correlated with the severity of liver disease and might be a potential noninvasive biomarker.